Structure, Nanomechanical Properties, and Wettability of Organized Erucamide Layers on a Polypropylene Surface - Gubała, Dajana (Langmuir : the ACS journal of surfaces and colloids, 2021)
Understanding the nanostructure and nanomechanical properties of surface layers of erucamide, in particular the molecular orientation of the outermost layer, is important to its widespread use as a slip additive in polymer materials. Extending our recent observations of nanomorphologies of erucamide layers on a hydrophilic silica substrate, here we evaluate its nanostructure on a more hydrophobic polypropylene surface. Atomic force microscopy (AFM) imaging revealed the molecular packing, thickness, and surface coverage of the erucamide layers, while peak force quantitative nanomechanical mapping (QNM) showed that erucamide reduced the adhesive response on polypropylene. Synchrotron X-ray reflectivity (XRR) was used to probe the out-of-plane structure of the surface layers. Static contact angle measurements further corroborated on the resulting wettability, also demonstrating the efficacy of erucamide physisorption in facilitating control over polypropylene surface wetting. The results show the formation of erucamide monolayers, bilayers and multilayers, depending on the concentration in the spin-cast solution. Correlation of AFM, XRR and wettability results consistently points to the molecular orientation in the outermost layer, i.e. with the erucamide tails pointing outward for the surface nanostructures with different morphologies (i.e., bilayers and multilayers). Rare occurrence of monolayers with exposed hydrophilic head groups were observed only at the lowest erucamide concentration. Compared with our previous observations on the hydrophilic surface, the erucamide surface coverage was much higher on the more hydrophobic propylene surface at similar erucamide concentrations in the spin-cast solution. Furthermore, the structure, molecular orientation and nanomechanical properties of the spin-cast erucamide multilayers atop polypropylene were also similar to those on industrially relevant polypropylene fibers coated with erucamide via blooming. These findings shed light on the nanostructural features of the erucamide surface layer underpinning its nanomechanical properties, relevant to many applications in which erucamide is commonly used as a slip additive